Systematic Literature Review: Validitas Internal dan Eksternal dalam Desain Ekperimen - Siska Merrydian; Indah Mustika Rini; Wardani Rahayu; Riyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In experimental research must have external and internal validity in order to control secondary variables. External validity relates to the generalization of research results, while internal validity relates to the extent of the causal relationship between the independent variable and the dependent variable. Therefore, it is important to examine internal and external validity in experimental design. The method used in this study is a systematic literature review. The database used for literature search utilizes two digital libraries, namely Google Scholar and Scopus. The literature search will take place in May 2024. In order for the selected literature to be relevant, the search uses the keyword